2008
DOI: 10.1016/j.corsci.2007.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion characterization of tin–lead and lead free solders in 3.5wt.% NaCl solution

Abstract: The corrosion resistance of Sn-Pb and several candidate lead free solders were investigated in 3.5wt.% NaCl solution through potentiodynamic polarisation. Results showed that in NaCl solution lead free solders had better corrosion resistance than SnPb solder and the corrosion resistance of lead free solders was similar, but the corrosion resistance of Sn-Ag solder was better than that of Sn-Ag-Cu and Sn-Cu solders. The corrosion products for Sn-Pb solder had a two-layered structure with Sn-rich phases at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(91 citation statements)
references
References 15 publications
2
69
1
1
Order By: Relevance
“…Once the corrosion has occurred, mechanical and electrical failures make the product stop. The corrosion properties of Sn-based lead-free alloys in corrosive environments have not been widely reported, even though it is important in many automotive, aerospace, maritime and defense applications [10]. Corrosion mainly originates either within the circuit (flux corrosion) or from the environment [11,12].…”
Section: Corrosionmentioning
confidence: 99%
“…Once the corrosion has occurred, mechanical and electrical failures make the product stop. The corrosion properties of Sn-based lead-free alloys in corrosive environments have not been widely reported, even though it is important in many automotive, aerospace, maritime and defense applications [10]. Corrosion mainly originates either within the circuit (flux corrosion) or from the environment [11,12].…”
Section: Corrosionmentioning
confidence: 99%
“…Therefore, there is also the potential for galvanically induced corrosion of the solder, which could exacerbate any atmospheric corrosion that might be occurring. However, the properties of these lead free alloys in corrosive environments has not been widely reported, though it is of importance in many automotive, aerospace, maritime and defence applications [46]. Some researchers have studied the corrosion behaviour of Sn-Zn-X solders [47,48] and Sn-Zn-Ag-Al-XGa [49], but few [50,51] have studied the corrosion properties of Sn-Ag, Sn-Cu and Sn-Ag-Cu solders.…”
Section: Corrosion Behavior Of Pb-free Soldermentioning
confidence: 99%
“…Nevertheless, the four Pb-free solders exhibit acceptable corrosion properties, since there is not much difference in key corrosion parameters between them and the Sn37Pb solder. The corrosion data of the solders in 3.5 wt.% NaCl solutions are listed in Tables 5 [46,51]. Lin and Mohanty et al [46][47][48][49] studied the corrosion properties of Sn-Zn-X and Sn-Zn-AgAl-XGa in NaCl solution, and their results showed that the corrosion product on the surface could be SnO, SnO 2 , SnCl 2 and ZnO, etc., depending on the applied potential.…”
Section: Corrosion Behavior Of Pb-free Soldermentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to develop lead-free solders, most research up to now focused on melting points and physical strengths of alloys, and there has been little consideration of the corrosion properties of base alloys for lead-free solders [8][9][10]. Moreover, the properties of these Sn-Bi-Sb lead-free alloys in corrosive environments have not been reported, and most of the fluxes are chloride or fluoride base compounds.…”
Section: Introductionmentioning
confidence: 99%